Executive function capacity links future thinking and exercise intent. Issue 4 (2nd October 2022) - Simmons, Chelsy S.; Schmidt, Adam T.; Lancaster, Brittany D.; Van Allen, Jason
Abstract: Objective: Environmental barriers limit exercise in adolescents, but the contribution of cognitive barriers are not as well characterized. Previous findings suggest future thinking may predict exercise intent, which has been linked to health and actual exercise. However, these models may be incomplete as they do not systematically incorporate potential cognitive contributions (e.g., executive function capacity) to exercise intent. This study investigated the possible mediating role of executive function capacity in the relation between future thinking and exercise intent. Methods: Data for the mediation models was collected from 101 adolescents aged 11–17 ( M =  13.09) in a summer enrichment program. Adolescent participants completed self-report measures including Consideration of Future Consequences Scale (CFCS), Intent to Exercise, and Behavior Rating Inventory of Executive Function, Second Edition (BRIEF-2). Results: This study found that self-reported executive function capacity mediated the relation between future thinking and exercise intent even when controlling for age and subjective socioeconomic status. Conclusions: While some exercise interventions aim to increase future thinking, this study provides support for additional research into how interventions may benefit from targeting executive function capacity directly to increase exercise intent and actual exercise.